The Role of Technology in Educational Media in the Disruptive Era - Kamaruddin Hasan; Safaruddin Safaruddin; Rahmi Rais (International Journal of Artificial Intelligence Research, 2022)
Technology in its development always brings changes to human life, especially in the world of education which will continue to experience changes. This article aims to determine the role of technology in educational media in an uncertain era. So it is hoped that educational technologists will no longer feel doubtful and interested in adapting and being able to take advantage of technology with all its benefits for educational life. The writing of this article uses the literature review method (library research), in which the researcher collects research-related materials from books, journals, scientific articles, literature and news from the mass media by describing and describing the data. Based on this discussion, it can be concluded that educational technology was created to solve learning problems by facilitating and providing new alternatives and innovations in the world of education. That way educational technology can make it easier to achieve educational goals.